Development of Digital Collections in Libraries and Archives in The Development of Economic Science in Bandung - Egi Abinowi; Aminudin; Haliatul Aulia Dzulfiqor; Resti Dewi Sri; Khansa Nurul Andini (Jurnal Informatika Ekonomi Bisnis, 2024)
With the rapid advancement of technology, libraries can now be accessed digitally. A digital library is an online or digital-based library that provides access to various types of books, journals, articles and other reading materials. Digital libraries provide services that allow users to read, download, or even search for specific materials they need without having to go to a physical library. Digital libraries can be accessed from anywhere and at any time, as long as there is an internet connection. In recent years, digital libraries have become increasingly popular due to their practicality and easy access to information and knowledge. The aim of this research is to develop library collections digitally; Facilitate access to information and knowledge from anywhere and at any time. Providing more effective and efficient library services using digital technology. Increasing the efficiency and effectiveness of library collection management.